A Study on the processing of the system of devshirme in high school history books in Turkey and Serbia - Kaya, Beytullah; Trifkoviç, Nada; Kaya, Beytullah (Mustafa Özgenel, 2019)
The establishment and expansion of the Ottoman Empire made it necessary to create new institutions in the field of state organization. The conquest of new land made possible by a strong administration and a strong military structure. Accordingly, the first state organization took place in the administration and military fields. In order to meet the needs of the soldiers and to create a strong military structure, at the beginning, the pencik system and then the devshirme system started to be implemented. This system which was implemented from 15th to 19th century became one of the bases of the Ottoman Empire. Devshirme system and its implementation achieved great social, political and military influence in the Ottoman Empire and the countries that were a part of it.Today, the devshirme system is described in different ways in the history books in the countries, which existed in the lands owned by the Ottoman Empire. This study intends to reveal how devshirme system is processed in the history books used in high schools in Serbia and Turkey. The research was realized through the document analysis of qualitative research methods. In this study it is shown that in Turkish high school history books devshirme system is handled in accordance with the academic commitment, while in the Serbian history books the concepts are including hostility. In addition, it is concluded that in the schoolbooks the devshirme system is processed according to the countriesʹ own perspectives.
Keywords: Devshirme System; Serbia; Turkey; High schools; History books